Experimental testing of methanol sorption on selected coal samples from Upper Silesian Basin - Baran, Paweł; Jodłowski, Grzegorz Stefan; Krzyżanowski, Andrzej; Zarębska, Katarzyna (Geology, Geophysics and Environment, 2015)
This paper summarises the results of methanol sorption on three selected coal samples from Polish collieries. These coals differ in terms of their degree of metamorphism (coal rank), petrography and elemental composition. It was found out that during the sorption of methanol, the sorption capacity is closely related to the structure of the coal surface and the amount of sorbed polar substance tends to decrease with the higher degree of metamorphism. Experimental data were plotted as isotherms. Empirical measurements were supported by thermodynamic analysis of aliphatic hydrocarbons sorption. The procedure is based on the Multisorption Model (MSM) designed for describing small molecules sorption in different types of carbonaceous materials (hard coals, lignites, active carbons).